HUBUNGAN POLA MAKAN DAN AKTIVITAS FISIK DENGAN STATUS GIZI PESERTA DIDIK MA DDI KANANG - S, Firman; Mushawwir Taiyeb, A; Halifah Pagarra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine whether there is a relationship between dietary patterns and physical activity with the nutritional status of students at MA DDI Kanang. The method used is quantitative with a correlational research design. The study population consisted of all students at MA DDI Kanang, with 142 respondents selected using purposive sampling. Data were collected using questionnaires on dietary patterns and physical activity, as well as nutritional status measurements through anthropometry. The results of the correlation test showed an R value of 0.330 and an R² value of 0.109, indicating that dietary patterns and physical activity simultaneously have a statistically significant relationship but with a low contribution level to nutritional status, which is 10.9%. Therefore, it can be concluded that there is a statistically significant but practically limited relationship between dietary patterns and physical activity with the nutritional status of MA DDI Kanang students.